Democracy Beyond Political Borders: An Introduction to the Special Issue. (6th October 2017) - Held, David; Schütze, Robert
Abstract : This Special Issue of Global Policy brings together a group of scholars from law, political science, philosophy, sociology, and history to discuss and assess the extent to which democracy can crystallise beyond the nation state, and whether such developments are, in principle, desirable.